Perspectives on Socio-environmental Transformations in Ancient Europe - Müller, Johannes; Kirleis, Wiebke; Taylor, Nicole (Quantitative Archaeology and Archaeological Modelling, 2024)
This open access book brings together key issues from transformative processes and events across Europe (and in some cases beyond) from 15,000 to 1 BCE. This volume covers the research output produced by the Collaborative Research Centre (CRC) 1266 "Scales of Transformation" - the first interdisciplinary centre to diachronically investigate transformations in past societies with a summary of their individual aspects from the Late Palaeolithic to the Roman Period. Following the introduction, the book is divided into three main sections: In "Identification of anatomies of socio-environmental transformation", the concept of scales of transformations is first explained, and the various parameters of transformational change are identified. This is followed by "Expressions of socio-environmental transformations: from climate preconditions to decision making", in which transformation processes are illustrated with individual examples. The third major part of the book deals with "Perspectives on decision making processes in socio-environmental transformations". In conclusion, the results are framed in a broad temporal framework, and patterns of socio-environmental change are presented across common time frames from the Eastern Mediterranean to Scandinavia. This book is of interest to researchers in archaeology and palaeoecology.